Connexin36 Expression in the Mammalian Retina: A Multiple-Species Comparison - Kovács-Öller, Tamás; Debertin, Gábor; Balogh, Márton; Ganczer, Alma; Orbán, József; Nyitrai, Miklós; Balogh, Lajos; Kántor, Orsolya; Völgyi, Béla (Frontiers in Cellular Neuroscience, 2017)
Much knowledge about interconnection of human retinal neurons is inferred from results on animal models. Likewise, there is a lack of information on human retinal electrical synapses/gap junctions (GJ). Connexin36 (Cx36) forms GJs in both the inner and outer plexiform layers (IPL and OPL) in most species including humans. However, a comparison of Cx36 GJ distribution in retinas of humans and popular animal models has not been presented. To this end a multiple-species comparison was performed in retinas of 12 mammals including humans to survey the Cx36 distribution. Areas of retinal specializations were avoided (e.g., fovea, visual streak, area centralis), thus observed Cx36 distribution differences were not attributed to these species-specific architecture of central retinal areas. Cx36 was expressed in both synaptic layers in all examined retinas. Cx36 plaques displayed an inhomogenous IPL distribution favoring the ON sublamina, however this feature was more pronounced in the human, swine and guinea pig while it was less obvious in the rabbit, squirrel monkey and ferret retinas. In contrast to the relative conservative Cx36 distribution in the IPL, the labels in the OPL varied considerably among mammals. In general, OPL plaques were rare and rather small in rod dominant carnivores and rodents, whereas the human and the cone rich guinea pig retinas displayed robust Cx36 labels. This survey presented that the human retina displayed two characteristic features, a pronounced ON dominance of Cx36 plaques in the IPL and prevalent Cx36 plaque conglomerates in the OPL. While many species showed either of these features, only the guinea pig retina shared both. The observed similarities and subtle differences in Cx36 plaque distribution across mammals do not correspond to evolutionary distances but may reflect accomodation to lifestyles of examined species.